The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fcvm.2021.665117
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Visit-to-Visit Mean Arterial Pressure Variability and the Risk of Heart Failure and All-Cause Mortality

Abstract: Background: Systolic or diastolic blood pressure (BP) variability is associated with an increased risk of cardiovascular events. We assessed whether BP variability measured by mean arterial pressure (MAP) was associated with increased risk of heart failure (HF) and death in individuals with or without hypertension.Methods: We evaluated 9,305 Atherosclerosis Risk in Communities (ARIC) study participants with or without hypertension and calculated BP variability based on MAP values from visit 1 to 4 [expressed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…And also there is a long-term visit-to-visit cohort study to explore the association between MAP and all-cause mortality among HF patients. In the study [ 34 ] evaluated 9305 participants, during a median follow-up of 16.8 years, found MAP as a main driving force for vital organ perfusion, was closely related to HF and all-cause mortality. MAP variability was associated with a higher risk of all-cause mortality and HF, indicating that MAP might be a potential risk factor for HF and death.…”
Section: Discussionmentioning
confidence: 99%
“…And also there is a long-term visit-to-visit cohort study to explore the association between MAP and all-cause mortality among HF patients. In the study [ 34 ] evaluated 9305 participants, during a median follow-up of 16.8 years, found MAP as a main driving force for vital organ perfusion, was closely related to HF and all-cause mortality. MAP variability was associated with a higher risk of all-cause mortality and HF, indicating that MAP might be a potential risk factor for HF and death.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, BP fluctuations have been perceived as inhibiting accurate BP measurement and as a phenomenon to be overcome by improved monitoring. 10 Recently, ample evidence 11 , 12 , 13 and our previous work 14 both indicated that elevated visit‐to‐visit BP variability could be a new risk factor for CVD. Unfortunately, the contribution of visit‐to‐visit BP variability to the residual cardiovascular risk remains unknown, which impedes the development of an optimum approach to the long‐term reduction of CVD events.…”
mentioning
confidence: 94%
“…Some studies have shown that BPV predicts cardiovascular events independently of mean blood pressure, 4,5 and that it is a better predictor than the mean blood pressure level 6 . Basson et al 7 demonstrated a correlation between long‐term BPV and the incidence of adverse events, such as death and heart failure, independent of hypertension 8 . However, several studies have indicated no significant association between long‐term BPV and cardiovascular events 9,10 or an increased risk of cardiovascular events is related to long‐term BPV only in patients with hypertension 11 .…”
Section: Introductionmentioning
confidence: 99%
“… 6 Basson et al 7 demonstrated a correlation between long‐term BPV and the incidence of adverse events, such as death and heart failure, independent of hypertension. 8 However, several studies have indicated no significant association between long‐term BPV and cardiovascular events 9 , 10 or an increased risk of cardiovascular events is related to long‐term BPV only in patients with hypertension. 11 Furthermore, a few studies have shown that short‐term BPV may better predict adverse cardiovascular events in young patients with hypertension, as well as mortality in older patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%